Ammonia plasma treatment as a method promoting simultaneous hydrophilicity and antimicrobial activity of viscose wound dressings. Issue 2 (January 2014) - Peršin, Zdenka; Zaplotnik, Rok; Kleinschek, Karin Stana
Viscose non-woven was treated by NH3 plasma. Different exposure times were used in order to find the optimum conditions for simultaneously improved hydrophilicity and antimicrobial activity, as desired effects by wound dressings. Both chemical and morphological modifications were studied by X-ray photoelectron spectroscopy and atomic force microscopy, respectively, revealing functionalization with nitrogen groups as well as formation of rich morphology at sub-micrometer scale. The wetting rise curves increased from 0.04 g 2  s –1 for non-treated material to 1 g 2  s −1 after prolonged treatment. The water contact angle decreased almost linearly with treatment time from 90° for non-treated samples to about 40° for samples treated for 140 s and remained rather constant thereafter. The AATCC 100–1999 standard test revealed reduction on all used bacteria, more pronounced for Gram-negative, that is, E. coli and P. aeruginosa, then for Gram-positive, that is, a significant for S. aureus and a marginal for E. faecalis .